2016
DOI: 10.1016/j.aprim.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Estudio coste efectividad del proceso diagnóstico de la trombosis venosa profunda desde la atención primaria

Abstract: The application of diagnostic algorithms when a DVT is suspected could lead to better diagnostic management by physicians, and a more cost effective process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…a good knowledge of ultrasound scanning techniques among family physicians could help cut the cost of medical care, since family physicians' ability to interpret the results correctly would most probably reduce the number of improper referrals to specialists [3]. For example, Fuentes Camps et al [17] examined the cost effectiveness of the application of diagnostic algorithms to patients with first episodes of suspected deep vein thrombosis in primary care, compared to systematic referral to specialist centers. they demonstrated that: (1) one third of all referrals to hospital emergency rooms could have been avoided, and that (2) the diagnostic cost could have been reduced by € 8,620 according to oudega and € 9,741 according to Wells, per 100 patients visited.…”
Section: Introductionmentioning
confidence: 99%
“…a good knowledge of ultrasound scanning techniques among family physicians could help cut the cost of medical care, since family physicians' ability to interpret the results correctly would most probably reduce the number of improper referrals to specialists [3]. For example, Fuentes Camps et al [17] examined the cost effectiveness of the application of diagnostic algorithms to patients with first episodes of suspected deep vein thrombosis in primary care, compared to systematic referral to specialist centers. they demonstrated that: (1) one third of all referrals to hospital emergency rooms could have been avoided, and that (2) the diagnostic cost could have been reduced by € 8,620 according to oudega and € 9,741 according to Wells, per 100 patients visited.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque la escala de Wells es la más utilizada en hospitales, en el trabajo "Estudio coste efectividad del proceso diagnóstico de la trombosis venosa profunda desde la atención primaria" [3] se comenta que ambas escalas presentan "sensibilidad y especificidad similar y no difieren en su validez diagnóstica. "…”
Section: Regla De Oudegaunclassified
“…Dicho diagnóstico debe realizarse con diversas entidades como celulitis, tromboflebitis superficial, rotura de quiste de Baker, desgarros musculares con hematoma, traumatismos de partes blandas, edema de estasis, síndrome postrombótico, artritis y linfedema [2]; aproximadamente, un 80-90% de los pacientes con clínica compatible con TVP, derivados desde la atención primaria, no presentan este diagnóstico [3]. Debido a ello, la TVP representa un desafío clínico para los médicos de todas las disciplinas, por lo que es esencial que el primer médico entre en contacto con la enfermedad para evaluar rápidamente, comenzar el tratamiento y remitir al paciente con el especialista [4], debido a que con el diagnóstico temprano es posible iniciar oportunamente el tratamiento que evite la manifestación pulmonar de la enfermedad.…”
Section: Introductionunclassified
“…The gold standard for diagnosis of DVT [14] is venography, which in addition to being invasive is highly expensive; hence, the most commonly used method in hospital emergency units is compression ultrasound [15]. However, none of the technologies mentioned is usually present in the primary care units [16], which is the first unit to which a patient comes to when feeling a symptom. In addition to this, the lack of experience of physicians regarding thromboembolic disease has caused legal situations where the main lawsuits cited "failure of physicians in the diagnosis and treatment of these diseases" [17].…”
Section: Introductionmentioning
confidence: 99%